Standard for Human Thrombin - Robertson, I; Gaffney, P. J; Bangham, D. R (Thrombosis and Haemostasis, 1975)
Ten laboratories took part in an international study of the proposed standard for human thrombin. A freeze-dried preparation (coded 70/157) was shown, using clotting time tests, to be suitable to serve as a standard for the assay of human and bovine thrombin preparations. The study shows that assay variation within laboratories was much less than between laboratories. The preparation was stable, having a negligible estimated loss of potency after ten years under the recommended storage conditions (—20° C in the dark).Each ampoule of the standard was assigned a potency of 100 units of thrombin activity, and one unit was defined as the activity contained in 0.0853 mg of the freeze-dried preparation.It was agreed by the participants in the study and by the International Committee on Thrombosis and Haemostasis (Vienna, 1973) that the thrombin preparation coded 70/157 is suitable to serve as an international standard for human thrombin.